"Cogito Ergo Sum"? Some issues about artificial intelligence and human will: A legal approach - Martinez de Campos, Mónica (2019)
When a person meets another one, sometimes has the strange feeling of "déjá vu", thinking "I met this person before". Psychology explains it as a path which is crossed between people. The same happens when people tries to predict the next friend they will meet. Which facts are most likely to lead to the connection? In the world of social networks, these are called nods. Each link shared among people is a line connecting them. In the computer world these graphs exist in an unlimited dimension, and artificial intelligence is calculating the importance of each edge, and distinguishing friends and enemies, important texts and insignificant publications putting all the numbers together and creating a composite profile of the most likely "normal" person. That profile is used for advertising purposes but also is used to the electronic hunt for terrorists. This bring us to a central problem: Are the artificial intelligence, which the path and the algorithm, really making choices and choosing for us? Descartes said "I think. I am", that's the course of humanity. Now computers are flummoxing the way we see the concepts of thought, will and action. Are these concepts exclusives to the mankind? With a view to developments in robotics and artificial intelligence, the Committee on Legal Affairs deemed it time for the European Union to act in respect of the legal and ethical issues raised by these new technologies. to this end, the JURI Committee set up a working group in 2015 with the primary aim of drawing up "European" civil law rules in this area, leading to the 2017's European Parliament's resolution on European Civil Law Rules on Robotics. Developments in civil robotics and artificial intelligence also call for reflection on the big ethical question they raise. In this regard, it is essential that the big ethical principles which will come to govern robotics and artificial intelligence develop in perfect harmony with Europe's humanist values. In this article we will try to establish the link between human will and electronic will, not forgetting that the thousands of world's leading computers, with billions of patterns and algorithms, will never replace the human perception of justice and fairness.